1994
DOI: 10.1002/prot.340180402
|View full text |Cite
|
Sign up to set email alerts
|

Correlated mutations and residue contacts in proteins

Abstract: The maintenance of protein function and structure constrains the evolution of amino acid sequences. This fact can be exploited to interpret correlated mutations observed in a sequence family as an indication of probable physical contact in three dimensions. Here we present a simple and general method to analyze correlations in mutational behavior between different positions in a multiple sequence alignment. We then use these correlations to predict contact maps for each of 11 protein families and compare the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
661
0
7

Year Published

1995
1995
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 830 publications
(674 citation statements)
references
References 15 publications
6
661
0
7
Order By: Relevance
“…Finally, we note that there has been interest in using information about correlated mutations to assist in the prediction of protein tertiary structure (Benner et al 1994a;Gobel et al 1994;Neher 1994;Shindyalov et al 1994;Taylor and Hatrick 1994). Generally, these analyses have been limited to looking at correlations between the residues found in current-day proteins.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, we note that there has been interest in using information about correlated mutations to assist in the prediction of protein tertiary structure (Benner et al 1994a;Gobel et al 1994;Neher 1994;Shindyalov et al 1994;Taylor and Hatrick 1994). Generally, these analyses have been limited to looking at correlations between the residues found in current-day proteins.…”
Section: Resultsmentioning
confidence: 99%
“…The results from this same program were also used as an independent P-strand secondary structure prediction method. Correlated mutations were calculated using the algorithm of Gobel et al (1994). The program takes a multiple sequence alignment of a protein family and tries to decode the observed mutational patterns in order to identify constrained sequence changes.…”
Section: Prediction Methodsmentioning
confidence: 99%
“…In this study, no correlation was found between residue covariation and residue proximity in the hydrophobic core. However, the possibility of using covariation as an indicator of structural proximity has been tested recently on a number of other protein sequence families, and weak, but possibly useful, correlations have been found in some cases (Gobel et al, 1994;Shindyalov et al, 1994). There is some disagreement as to whether such pairwise correlations provide additional information beyond that of a simple conservation metric, but differences in methodology make comparisons difficult (Taylor & Hatrick,I 994).…”
Section: Discussionmentioning
confidence: 99%
“…A number of recent papers have examined the relationship between residue correlations and structure (Gobel et al, 1994;Neher, 1994;Shindyalov et al, 1994;Taylor & Hatrick, 1994). However, as noted by these authors and others, apparent correlations can also arise from biases in the sequence set.…”
mentioning
confidence: 99%